2022
DOI: 10.3343/alm.2022.42.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Characteristics of Urinary Red Blood Cell Distribution Incorporated in UF-5000 for Differentiation of Glomerular and Non-Glomerular Hematuria

Abstract: Background: Automated urine sediment analysis has been developed to address the limitations of microscopic examination of dysmorphic red blood cells (RBCs). We evaluated the urinary RBC distribution (URD) parameter of a recently launched automated urinary flow cytometry analyzer, UF-5000 (Sysmex, Kobe, Japan), to differentiate glomerular hematuria (GH) from non-GH (NGH).Methods: Samples submitted for urine sediment analysis from patients with hematuria ( > 20 RBCs/μL) were divided into derivation (N = 156; 101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Flow cytometers have also been used to differentiate the glomerular and non-glomerular origin of hematuria, albeit with conflicting results [ 19 ]. While the sensitivity of the method has been found to be low for differentiation in previous studies, newer devices appear to be more accurate in this regard [ 20 ]. Nonetheless, extensive clinical trials are still lacking and the final assessment should be made by an experienced and knowledgeable medical eye [ 19 , 20 ].…”
Section: Diagnostic Procedures In the Investigation Of Hematuriamentioning
confidence: 99%
“…Flow cytometers have also been used to differentiate the glomerular and non-glomerular origin of hematuria, albeit with conflicting results [ 19 ]. While the sensitivity of the method has been found to be low for differentiation in previous studies, newer devices appear to be more accurate in this regard [ 20 ]. Nonetheless, extensive clinical trials are still lacking and the final assessment should be made by an experienced and knowledgeable medical eye [ 19 , 20 ].…”
Section: Diagnostic Procedures In the Investigation Of Hematuriamentioning
confidence: 99%
“…The screening performance of urine testing for UTIs is widely recognized ( 18 - 21 ). In addition, automated urine sediment analyzers have been used to differentiate between glomerular hematuria (GH) and non-glomerular hematuria (NGH) ( 22 ). Urine testing can also be predictive of suspected uroepithelial cancer ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Urine RBC counts can be measured using automated urine sediment analyzers [ 4 ]. A previous study suggested that the determination of urinary RBC distribution with an automated analyzer and analysis of the distribution curves may be a more reliable measure of erythrocyte morphology [ 18 ]. Renal biopsy, the gold standard for the diagnosis of kidney diseases, can be used to verify the sources of urinary RBCs, and the count and morphology of urinary RBCs can, in turn, provide important information on patients’ renal pathological changes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%